2015
DOI: 10.3390/cli3040983
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Information, and Views of Climate Change: An Examination of Coastal Stakeholders along the Gulf of Mexico

Abstract: Abstract:The ability to understand complex issues is essential to adequately evaluate risk and policy alternatives. Stakeholders are more likely to understand and influence these issues. While stakeholders that specialize in coastal regions have many issues that demand their attention, there are a few that potentially affect everyone within this community. We utilize in-depth interviews to examine climate change attitudes, and the influence of knowledge, information, and institutions within a sample of stakeho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…The literature shows that objective and perceived knowledge is associated with people's attitudes (Stoutenborough et al, 2013; Stoutenborough & Vedlitz, 2015; Zhang et al, 2020). The objective knowledge variable was calculated as the percentage of correct answers to six true/false statements: (1) “Genes are a basic driver of heredity” (True); (2) “Genetic engineering of crops has not yet been used to manage agricultural pests” (False); (3) “People receive all of their genes from only one of their parents” (False); (4) “A keystone species is one that is critical to a particular ecosystem” (True); (5) “U.S.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The literature shows that objective and perceived knowledge is associated with people's attitudes (Stoutenborough et al, 2013; Stoutenborough & Vedlitz, 2015; Zhang et al, 2020). The objective knowledge variable was calculated as the percentage of correct answers to six true/false statements: (1) “Genes are a basic driver of heredity” (True); (2) “Genetic engineering of crops has not yet been used to manage agricultural pests” (False); (3) “People receive all of their genes from only one of their parents” (False); (4) “A keystone species is one that is critical to a particular ecosystem” (True); (5) “U.S.…”
Section: Methodsmentioning
confidence: 99%
“…Numerous studies on public opinion toward science suggest that multiple factors influence a citizen’s choice to trust in science. These factors include perceptions of risks, values, and beliefs (Bauer et al, 2007; Kellstedt et al, 2008; Stoutenborough & Vedlitz, 2015; Sturgis & Allum, 2004); political orientation (Hochschild et al, 2012; McCright et al, 2013; McCright & Dunlap, 2011); religious orientation (Brossard et al, 2009; Sturgis & Allum, 2004); and sociodemographic factors (Chao & Wei, 2009; Nisbet et al, 2002).…”
Section: Trust In Science Scientists and Policy Supportmentioning
confidence: 99%
See 1 more Smart Citation
“…Past literature generally suggests two groups of influential factors. The first group of factors is linked to citizens' individual level factors, including personal background variables such as race, gender, education, and income (Chao & Wei, 2009;McCright et al, 2013;Nisbet et al, 2002;Xiao, 2013), religious orientation (Brossard et al, 2009;Gauchat, 2008Gauchat, , 2012Nisbet, 2005;Sturgis & Allum, 2004), technology-specific knowledge (Gauchat, 2011;Nisbet, 2005;Stoutenborough & Vedlitz, 2015), political orientation (Hochschild et al, 2012;McCright & Dunlap, 2011;McCright et al, 2013;Mooney, 2012), and personal perceptions and beliefs such as perceived benefits and risks, trust in institutions, and worldviews (e.g., Knight, 2006;Siegrist, 1999Siegrist, , 2000Siegrist et al, 2000;Yang & Hobbs, 2020). These individual level factors function as personal level filters through which individuals form their views about technological innovations.…”
Section: Literature Review and Theoretical Expectationmentioning
confidence: 99%
“…Compounding this already complex restoration effort are attitudes about climate change and its anticipated effects. For example, a study of coastal stakeholders on the Gulf Coast found that government employees were likely to be more skeptical of accepting climate change (Stoutenborough and Vedlitz 2015) than other coastal stakeholders, though climate change is a polarizing issue for the general public as well. This increases the difficulty for political decisionmakers to consider sea level rise as an explicit threat to project success.…”
Section: Dwh Funding Processes and Restoration Targets -An Unprecedenmentioning
confidence: 99%